Home Movies And The Nigerian Youths: A Study On The Morals And Cultural Values In Delta State - Ivwighren, Hannah; Irori, Okiemute Queenett; Ivwighren, Hannah Emuobosa; Queenett, Irori Okiemute Queenett (The Indonesian Journal of Social Studies, 2023)
The study is mainly based on the impact of home movies on the morals and cultural values of Nigerian youths in Delta state. With a survey approach, 225 participants from Abraka Grammar School, University Secondary School and Ojeta Secondary School were sampled by using purposive sampling techniques. Copies of a structured questionnaire were distributed to students to collect information on their perceptions regarding the dressing styles, fashion depictions in home videos, and the effects of the same on cultural behavior and economic trends. It is seen that students' evaluations of dressing styles and fashion trends under study of home videos have the strongest effect on cultural values of young Nigerian adults in Delta State. Therefore, it is worth mentioning that the economy of individuals living in Delta is also affected by the actions of the Nigerian youths who watch home movies. Suggestions include encouraging limitation on the watching of movies that are not virtuous, but rather use of those that may seem helpful for the same. However, this may not be a practical measure to reduce immoral behavior. Furthermore, the emphasis must be put more on the positive aspects of the films found in the home movie.